ADIPOQ, KCNJ11 and TCF7L2 polymorphisms in type 2 diabetes in Kyrgyz population: A case‐control study. Issue 2 (23rd November 2018) - Isakova, Jainagul; Talaibekova, Elnura; Vinnikov, Denis; Saadanov, Iskender; Aldasheva, Nazira
Abstract: The aim of this study was to ascertain the polymorphic markers profile of ADIPOQ, KCNJ11 and TCF7L2 genes in Kyrgyz population and to analyze the association of polymorphic markers and combinations of ADIPOQ gene's G276T locus, KCNJ11 gene's Glu23Lys locus and TCF7L2 gene's VS3C>T locus with type two diabetes (T2D) in Kyrgyz population. In this case‐control study, 114 T2D patients 109 non‐diabetic participants were genotyped using polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP). Two individual polymorphisms ( ADIPOQ rs1501299, KCNJ11 rs5219) were found to be associated with T2D. We found two (Lys23Lys/CC and Glu23Lys/CT) of the overall nine combinations, which were more prevalent in T2D group compared to controls (χ 2 = 4.21, P = 0.04). Lys23Lys/CC combination was associated with a 2.65‐fold increased likelihood of T2D (OR = 2.65, 95% CI 1.12‐6.28), whereas the Glu23Lys/CT combination also increased such likelihood (OR = 3.88, 95% CI 1.27‐11.91). This study demonstrated some association of 276T allele and ADIPOQ gene G276T heterozygous genotype as well as KCNJ11 gene 23Lys allele with T2D in ethnic Kyrgyz, but study results should be interpreted with caution because of the limited statistical power.